PROBLEMATIKA PENERAPAN TAJWID DALAM TILAWAH AL-QURA’AN PADA KOMUNITAS PERDESAAN - Badliatul Anisyah Dalimunthe; Zaianal Efendi Hasibuan; Sawaluddin Siregar (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
Rural communities in general can read the Quran without spelling it out. However, they still pay less attention to Tajweed, starting from the length, the nature of the letters, and the makhorijul of the letters, also due to the lack of attention from parents and the surrounding community. And in TPA, those who have studied Tajweed Science have not been able to apply it to the readings they read, plus there are still small children who are not able to distinguish one letter from another so they need special attention. This mentoring method uses the PAR (Participatory Action Research) method, which is research by identifying a problem in the field, then entering an action as an answer or solution to the problem that has been identified. Initial Identification activities with in-depth interviews with TPA teachers. Then continued to the Problem Solving stage by collecting data and information from parents regarding obstacles to learning tajwid, and the last stage is Action As Solution, namely creating reading activities using correct tajwid and mentoring in the form of coaching and training guidance for the community, especially children. The results of this service are that children can read the Koran fluently and use correct tajwid.